Peripheral BDNF Response to Physical and Cognitive Exercise and Its Association With Cardiorespiratory Fitness in Healthy Older Adults - Tarassova, Olga; Ekblom, Maria M.; Moberg, Marcus; Lövdén, Martin; Nilsson, Jonna (Frontiers in Physiology, 2020)
Physical exercise (PE) has been shown to improve brain function via multiple neurobiological mechanisms promoting neuroplasticity. Cognitive exercise (CE) combined with PE may show better effect on cognition. Brain-derived neurotrophic factor (BDNF) is important for neuroplastic signaling and may be reduced with increased age. The source and physiological roles of BDNF that can be measured in human peripheral blood plasma (pBDNF) and serum (sBDNF) are thought to differ. An intervention study in healthy older adults investigated the effects of acute (35 min) and prolonged (12 weeks, 30 sessions) CE and PE alone and in combination on pBDNF and sBDNF, and cross-sectional associations between baseline pBDNF, sBDNF and cardiorespiratory fitness (CRF). Participants (65-75 years) were randomized into four groups prescribed either: CE plus 35 min of rest (n=21, 52% female), PE plus 35 min of rest (n=27, 56% female), CE plus PE (n=24, 46% female) or PE plus CE (n=25, 52% female). Groups were tested at pre and post 12 weeks of training intervention. Blood was collected at baseline, after the 1st and 2nd exercise (or rest) at both pre and post. CRF was assessed using a submaximal ergometer test (EB) and a maximal treadmill ergometer test (VO2max) 48 hours prior to the test sessions. At both pre and post, pBDNF increased after CE and PE (up to 222%), and rest (~67%), whereas sBDNF increased only after PE (up to 18%) and returned to its baseline after rest. Acute but not prolonged PE increased both pBDNF and sBDNF. CE induced acute changes in only pBDNF. Baseline pBDNF and sBDNF were positively associated (n=93, r=0.407, p<0.001). Prolonged PE improved average EB in the three groups prescribed PE, while no changes in VO2max were shown. Baseline CRF did not correlate with baseline BDNF. Even though baseline pBDNF and sBDNF were associated, patterns of changes in pBDNF and sBDNF in response to exercise were explicitly different. Future research should study how pBDNF and sBDNF differ between blood entering and leaving the brain, to better understand under what circumstances peripheral BDNF could be a result of elevated secretion or availability of central BDNF in humans.